Laser light illuminates medical research - Price, Kylie; Berridge, Mike (New Zealand Science Review, 2015)
​Light in the form of lasers has played a key role in biomedical research and advancing human health over the past 61 years. Today, most people are familiar with lasers, but many do not fully appreciate the descriptive acronym: Light Amplification by Stimulated Emission of Radiation. The process called ‘Stim-ulated Emission’that underpins lasers was first conceived and developed by Albert Einstein in 1917. Before delving into the use of lasers in medical research, a brief introduction to this revolutionary light source is warranted.